2023
DOI: 10.3390/healthcare11162260
|View full text |Cite
|
Sign up to set email alerts
|

Potential Effect of Combined Exposure of Crystalline Silica Dust and Cigarette Smoking on the Incidence of Silicosis among Chinese Male Stone Processing Workers: A Cross-Sectional Study

Abstract: Background: Silicosis is a progressive and irreversible disease primarily caused by exposure to crystalline silica dust and, to a lesser extent, cigarette smoking. However, further research is needed to validate the potential combined effect of these risk factors on the increased incidence of the disease. Methods: A total of 1688 male workers employed at a Chinese stone processing plant between 1 January 1999 and 31 December 2019, were included in the study. Cumulative exposure to industrial crystalline silica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…For example, a recent study that focussed specifically on workers exposed to ES dust found an association between smoking history and risk of disease [ 3 ], in line with work in pottery workers [ 66 ]. Another cross-sectional study of natural stone fabricators found that, while prolonged cigarette smoking was not significantly correlated with X-ray evidence of lung silicosis (OR 1.59, 95% CI 1.00 to 2.53) [ 67 ], there was evidence of additive effects of cigarette smoke and dust exposure on disease risk. Similar complexity was observed in a small cohort of workers processing ES, whereby smoking status was not associated with silicosis in ES workers, but was correlated with declines in lung function in those with disease [ 68 ].…”
Section: The Hostmentioning
confidence: 99%
“…For example, a recent study that focussed specifically on workers exposed to ES dust found an association between smoking history and risk of disease [ 3 ], in line with work in pottery workers [ 66 ]. Another cross-sectional study of natural stone fabricators found that, while prolonged cigarette smoking was not significantly correlated with X-ray evidence of lung silicosis (OR 1.59, 95% CI 1.00 to 2.53) [ 67 ], there was evidence of additive effects of cigarette smoke and dust exposure on disease risk. Similar complexity was observed in a small cohort of workers processing ES, whereby smoking status was not associated with silicosis in ES workers, but was correlated with declines in lung function in those with disease [ 68 ].…”
Section: The Hostmentioning
confidence: 99%